Negotiating Ability of Using Condom to Prevent Sexually Transmitted Disease and HIV/AIDS of Commercial Sex Worker Woman in Region Surakarta - Widodo, Arif; Kaeksi, Retno Woro (Forum Geografi, 2005)
The data from Board of Health in Surakarta City, on 8 September 2005, from 155 commercial sex worker woman had blood examined, there were 7 persons positive in HIV. One of factor affecting the high infection HIV/AIDS in women commercial sex worker was low use of condom. Aims of this research was to know factor-factor associated with didnât use of condom and social aspect negotiations about using condom (education, economics status, working experience, devilling place, occupation, ethnic, religious, and income). This research is qualitative research using guided group discussion technique, in-depth interview, and participatory observation. Subject for this research were 30 persons, consist of 25 commercial sex worker, 3 guest, 1 room owner, and 1 parent. Independent variables in this research are social economics characteristic, demography and community characteristics. Dependent variables as PPSK capability in condom using negotiating to prevent sexually transmitted disease and HIV/AIDS. Commonly, despite knowing that everyone, including themselves, is vulnerable to AIDS infection, the respondents ignore asking the guest/partners for condom use. Most of them donât ask for condom use due to their fear of either being the target of the guest anger and bad words, or losing money from them. Women commercial sex worker Silir in using condom and prevent sexual transmitted disease had free education from Board of Health in Surakarta City. In the street prostitutes are low support from peer, room owner, hotel owner, or guest about using condom for women commercial sex worker in illegal place, caused women commercial sex worker in the street more potential and high risk to spread sexual transmitted diseases than they were operated in Silir. The low capability of the street prostitutes for negotiating condom use with the guest customers results from: misperception on "safe-sex" behavior for seeking "help", economic and psychology pressure, free and uncontrolled companion relationship unavailability of condom in the room. This research result serve as an assessment study of the need which will be developed into a comprehensive promotion strategy.